The Effect of Fertilization with Antibiotic-Contaminated Manure on Microbial Processes in Soil - Jadwiga Wyszkowska; Dariusz Mikulski; Agata Borowik; Magdalena Zaborowska; Jan Kucharski; Krzysztof Kozłowski; Magdalena Bilecka; Anna Gajda; Konrad Pietruk; Piotr Jedziniak; Katarzyna Ognik; Jan Jankowski (Agriculture)
Antibiotics are a great blessing for humanity, and they have saved millions of human lives. Antimicrobials have enabled humans to produce animal-based foods that are free of pathogens. However, antibiotics also have a number of weaknesses. The use of antimicrobials in livestock production can have adverse consequences for the natural environment. The aim of this study is to evaluate the applicability of manure from turkeys administered monensin (M), enrofloxacin (E), and doxycycline (D) as soil fertilizer and to determine the impact of these antibiotics on the physicochemical, microbiological, and biochemical properties of soil in a pot experiment. The following treatments were established: unfertilized soil (S), soil fertilized with turkey manure free of antibiotics (C), soil fertilized with turkey manure containing only M (M), soil fertilized with turkey manure containing M and E (ME), and soil fertilized with turkey manure containing M, E, and D (MED). The experimental plant was Zea mays. The study demonstrated that the soil application of turkey manure containing all three antibiotics (MED) did not inhibit the growth of Zea mays, did not lead to adverse changes in the physicochemical properties of soil, and did not disrupt the abundance or diversity of culturable microorganisms, despite the fact that these antibiotics were identified in both the soil and Zea mays roots. The application of manure containing M, E, and D in the cultivation of Zea mays contributed to the transfer and presence of E and D in soil and maize roots. Antibiotics were not detected in above-ground plant parts. Monensin was not identified in soil or plant samples. The tested manure induced significant changes in the biochemical index of soil quality and in the microbiome of non-culturable bacteria and fungi at both phylum and genus levels. These results indicate that manure from turkeys administered M, E, and D should be used with caution to avoid permanent changes in the microbiome and biochemical properties of soil. Manure contaminated with antimicrobials can be used in the production of fodder crops that do not accumulate antibiotics in above-ground parts.